2011
DOI: 10.1016/j.nuclphysb.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Frame-like actions for massless mixed-symmetry fields in Minkowski space. Fermions

Abstract: A frame-like action for massless mixed-symmetry fermionic fields in Minkowski space is constructed. The action is uniquely determined by gauge invariance. * skvortsov@lpi.ru † yurii.zinoviev@ihep.ru

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…t 1 t 2 p ðkÞ! abjcd m ðqÞ Â nm pd 1 36 s 1 a s 2 b t 1 c q t 2 þ 4 3 t 1 a s 1 b t 2 c k s 2 þ 1 12 s 1 t 1 s 2 a t 2 b k c À s 1 t 1 s 2 a t 2 c p b þ Symmðm; a; bÞ : (48) This concludes the calculation of the 3-derivative part of the cubic vertex. Inclusion of the appropriate Chan-Paton's indices is straightforward and leads to vertices of the type considered in [20,73].…”
Section: Three-point Amplitude and 3-derivative Vertexmentioning
confidence: 54%
“…t 1 t 2 p ðkÞ! abjcd m ðqÞ Â nm pd 1 36 s 1 a s 2 b t 1 c q t 2 þ 4 3 t 1 a s 1 b t 2 c k s 2 þ 1 12 s 1 t 1 s 2 a t 2 b k c À s 1 t 1 s 2 a t 2 c p b þ Symmðm; a; bÞ : (48) This concludes the calculation of the 3-derivative part of the cubic vertex. Inclusion of the appropriate Chan-Paton's indices is straightforward and leads to vertices of the type considered in [20,73].…”
Section: Three-point Amplitude and 3-derivative Vertexmentioning
confidence: 54%
“…As a matter of fact, vanishing of p ½c à ab -type insertions to correlators is just a particular example of a general property of S-matrix elements of s ¼ 3 vertex operators coupling 3-tensors with hooklike Young diagrams-It can be shown that such operators do not contribute to S-matrices, which is reminiscent of what happens in the framelike approach [11,42,[49][50][51], where contributions with hooklike symmetries are eliminated by algebraic constraints. Therefore, the correlators are invariant under shifting symmetric tensor H abc by symmetrized derivative of Ã, implying the gauge symmetry (6) in the field theory limit.…”
Section: Introductionmentioning
confidence: 98%
“…It seems that the frame-like approach contains more information about interactions even at the linear level. Another example of this phenomenon was observed in [57], where a simple argument prevents constructing Lagrangians for certain types of fermionic fields, which is highly nontrivial to see in the metric-like approach [58,59]. The gravitational interactions for fields that are described by forms of higher degree in the frame-like approach are severely constrained, see e.g.…”
Section: Discussionmentioning
confidence: 99%